Konsep Pidana Mati dan Pandangan Subjektif Hukum Terhadap Rentang Waktu Eksekusi Mati di Indonesia - Mohammad Batu (Jurnal Hukum Bisnis, 2023)
The imposition of the death penalty by a judge on a death row convict is the heaviest sentence in convicting a defendant in court, the imposition of the death penalty is the fairest possible sentence. The aim of this research is to provide an overview of the concept of the death penalty and the legal subjective view of the time span for executions in Indonesia. The research method used is normative literature. The death penalty in Indonesia needs to be applied as the heaviest punishment given by the defendant or convict because the death penalty is the heaviest punishment and is a form of criminal law's firmness in law enforcement in Indonesia. Next, it is necessary to look at the time span after a death row convict receives a death sentence.